Assessment Of Factors Affecting Long-Term Usage In Scleral Lens Wearers: A Prospective Study. - Gupta, Deepak; Ahluwalia, T. S.; Jain, Vivek Kumar (Journal of Neonatal Surgery, 2025)
Introduction: To assess factors influencing the long-term usage of scleral lenses among wearers evaluating both subjective experiences and clinical parameters. Methods: A prospective study was conducted on new scleral contact lens wearers. Details of enrolled patients was collected using validated questionnaire. Clinical data including lens parameters (diameter, material), wearing time (hours/day, days/week), and ocular findings (conjunctival redness, corneal staining) were recorded. Statistical analyses were performed to identify significant factors associated with sustained scleral lens usage. Results: The study included 40 study scleral lens wearers with mean age 42.5 ± 12.4 years and predominantly female(60%). longer wearing duration correlated positively with higher satisfaction scores (p < 0.001), better lens comfort (p = 0.002), and fewer adverse symptoms (p = 0.01). Difficulty in lens handling and midday fogging were common challenges impacting long-term use. Conclusions: This study suggested that subjective satisfaction, comfort, and ease of lens handling are critical factors for long-term scleral lens usage.